2016
DOI: 10.20960/nh.404
|View full text |Cite
|
Sign up to set email alerts
|

Defi ciencia clínica de vitamina A tras bypass gástrico. Descripción de un caso clínico y revisión de la literatura

Abstract: Vitamin A defi ciency is uncommon in developed countries. Bariatric surgery emerges a an important risk factor for vitamin A defi ciency and some clinical cases have been described, specially associated with malabsorptive surgical techniques, such as biliopancreatic diversion. In this paper we report a clinical case of a patient who developed blindness, ophthalmological disease and cutaneous alterations secondary to vitamin A defi ciency after gastric bypass. A review of other publications and recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In gastric bypass, a prevalence of 11% has been reported, and it is associated with visual symptoms such as xerophthalmia or night vision impairment [ 114 ]. In a prospective study in GBP patients, decreased levels were observed in 37.5%, 50.8%, and 52.9% preoperatively, at 30 days, and at 180 days, respectively [ 115 ]. Clinical vitamin A deficiency, manifested by visual and skin changes, is less common.…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%
“…In gastric bypass, a prevalence of 11% has been reported, and it is associated with visual symptoms such as xerophthalmia or night vision impairment [ 114 ]. In a prospective study in GBP patients, decreased levels were observed in 37.5%, 50.8%, and 52.9% preoperatively, at 30 days, and at 180 days, respectively [ 115 ]. Clinical vitamin A deficiency, manifested by visual and skin changes, is less common.…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%